2013
DOI: 10.1089/jmf.2013.2790
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects of Dietary Nucleotides in Second-Generation Weaned Rats

Abstract: The aim of the present study was to evaluate dietary effects of dietary nucleotides (NTs) on developmental parameters in second-generation Sprague-Dawley rats. Experimental design was set up as six groups, including one control and five nucleotide administered groups, doses ranged from 0.01% to 1.28% nucleotides. First-generation (F0) rats were divided into two terms: (1) fed for 90-day study; (2) mated for offspring (F1). After weaning, each group of second-generation F1 rats was fed the control diet. Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…In addition, there were no adverse effects up to the dose of 1.28%. 31 The 0.04% and 0.16% NTs could reverse the above markers to attenuate alcohol-induced liver injury in the present study. Inflammation is one of the vital characteristics of alcoholic hepatitis.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, there were no adverse effects up to the dose of 1.28%. 31 The 0.04% and 0.16% NTs could reverse the above markers to attenuate alcohol-induced liver injury in the present study. Inflammation is one of the vital characteristics of alcoholic hepatitis.…”
Section: Discussionsupporting
confidence: 55%
“…For the filial part, there were no significant differences in physical or neural development landmarks between the control and NT groups. However, in previous study [17,22], NTs consumption could promote growth and development in weaned rats. It has been suggested that NTs could reduce the incidence of diarrhea, possibly by a favorable effect on the gastrointestinal microbiota, in formula-fed infants.…”
Section: Discussionmentioning
confidence: 77%
“…The healthy development of early gut villi improves the digestion and absorption of nutrients in infants (He et al., 2020). NTs promote the development of gut villi, improve digestion and nutrient uptake, and promote weight gain in infants (Xu et al., 2013). Exogenous NTs significantly enhance gut villus proteins and the characteristic factors of mature enterocytes and enable villus development (Rodriguez‐Serrano et al., 2010).…”
Section: Effects Of Dietary Nts On Gut Development and Function In Ea...mentioning
confidence: 99%